Fruitshop economics - Hayward, Nick; Garner, Simon; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2005)
This fast-paced program examines basic economic concepts in a way that students will easily understand and relate to. The concepts of Markets, Demands, Production, Supply, Competition and the Role of the Government are explored in the text of a successful family business
Title from title screen
Executive producer, Mark McAuliffe ; camera, Ben HArding, Nick Hayward ; sound, Wayne Martin
Voice over: Mike Newman
Keywords: Economics; Business